Interventions/Adaptive Reuse - Berger, Markus; Wong, Liliane (Providence : Department of Interior Architecture, Rhode Island School of Design, 2013)
Int/AR is a yearly publication on current issues in international adaptive reuse and interior architecture. Int/AR looks at interior architecture as one of the professions that shape our built environment. This volume on buildings with a difficult history that are to become memorial places deals with trauma, narration and recollection in adaptive reuse projects.
Includes bibliographical references : (pages 120-128).
Keywords: Public buildings -- Remodeling for other use -- Psychological aspects; Public buildings -- Remodeling for other use -- Social aspects; Historic buildings -- Remodeling for other use; Memory